Powering the lean enterprise : how to streamline operations, improve quality, and gain customer loyalty - Artzberger, Bill (PMP, LSSBB) (Routledge, Taylor & Francis Group, 2025)
In this book, you will learn about: -- Lean thinking. -- Lean mindset. -- The four Lean rules and five Lean principles. -- The Lean transformation roadmap. -- Lean leadership -- Five common Lean pitfalls and how to avoid them -- Kaizen workshops -- Daily improvements and Kata.
"A Productivity Press book".
Keywords: Lean manufacturing.; Leadership.; Organizational effectiveness.; Business enterprises.; elektronické knihy; electronic books